The implementation of the International Hydrographic Organisation's Worldwide Electronic Navigational Chart Data Base for Electronic Chart Display and Information Systems : the implications to sub-Saharan Africa - Osei, Samuel (School of Architecture, Planning and Geomatics, 2017)
This report gives suggestions to sub-Saharan Africa regarding the implementation of the International Hydrographic Organisation's (IHO) Worldwide Electronic Navigational Chart Data Base (WEND) for Electronic Chart Display and Information _systems (ECDIS). The IHO, recognising the need to supply up-to-date navigational information to mariners at sea, proposes the establishment of a worldwide network of navigational information. This proposal is aimed at addressing the information needs of international shipping. However, it does not restrict any hydrographic office from developing its own data base for national shipping. ECDIS is one new technology that will improve safety at sea. It integrates the Electronic Navigational Chart (ENC) and other navigational information. Unlike the paper chart, ECDIS will select and display information that is needed at any chosen moment thereby removing clutter from the display. The mariner will only see the information that is relevant for his immediate decision-making. ECDIS is versatile, complex and a potentially important aid to navigation decision-making. It enables mariners to navigate under conditions of poor visibility and through narrow and poorly-marked channels. It has the power to process data from a variety of sources and to detect and graphically show relationships between the data. Since history requires us to look at the past and the present to be able to project into the future, the report begins by giving the background to electronic charts. The report examines the traditional paper chart and the present method of updating the chart. It looks at the information contained in the Notices to Mariners, Radio Navigational Warnings and Global Maritime Distress and Safety Systems. The responsibilities and obligations of the various professional disciplines involved in updating the paper chart are also discussed. The limitations of the paper chart are commented upon and the need for a new technology is emphasized. The procedure for updating the electronic chart is also discussed. The terms "paper chart" and "traditional paper chart" are used interchangeably and mean the same thing in this report. The second chapter examines the requirements of ECDIS. It discusses the user requirements and the minimum system configuration. Operational and performance requirements are also examined. Chapter Three discusses the Worldwide Electronic Navigational Chart Data Base (WEND). It gives a brief background to WEND and discusses the conceptual model of the organisation of WEND on regional bases. It examines a paper presented by Australia in relation to a single state WEND proposed by Norway. Since the whole process of networking the navigational information depends on technology, an in-depth treatment of the subject is carried out in Chapter Four. Issues discussed include networking and distributed system, standards and protocols in telecommunications. The design consideration for the infrastructure for a Regional Electronic Navigational Chart Coordinating Centre (RECC) is dealt with in Chapter Five. Financial and institutional issues are discussed. Technical and non-technical security measure are commented upon. Chapter Six deals with the infrastructure design for a RECC. It examines the infrastructure components, system operation and maintenance and manpower. Strategies for implementing RECC in the sub-Saharan Africa are discussed in Chapter Seven. Network development, data and system security measures are commented upon. Chapter Eight looks at the legal implications of ECDIS and WEND. It examines the elements of the legal regime and speculates on the possible changes that could be brought about as a result of the changing technology. Chapter Nine concludes the report with recommendations on a regional WEND centre.